Osteoarthritis: multitissue pathology, molecular mechanisms, clinical management, and emerging precision and regenerative therapies - Qiu, Lina; Alhaskawi, Ahmad; Moqbel, Safwat Adel Abdo (Frontiers in Pharmacology, 2026)
Osteoarthritis (OA) is a progressive, whole-joint disorder driven by a convergence of biomechanical stress, inflammation, metabolic dysfunction, and cellular senescence. This review integrates recent advances in our understanding of the distinct yet interconnected pathological processes affecting articular cartilage, subchondral bone, synovium, infrapatellar fat pad, menisci, ligaments, and peri-articular musculature. Emerging mechanisms, such as chondrocyte ferroptosis, neurovascular remodeling, and synovial-mesenchymal reprogramming, are highlighted for their roles in disease propagation and chronic pain. We critically appraise current therapeutic modalities, including evidence-based non-pharmacological strategies, pharmacologic agents, intra-articular biologics, and surgical interventions. In parallel, we explore the promise of precision medicine, multi-omics profiling, advanced imaging biomarkers, regenerative therapies, and artificial intelligence in reshaping diagnostic and treatment paradigms. This comprehensive synthesis underscores the shift toward a mechanistic, individualized approach to OA management and identifies key translational opportunities for disease modification and early intervention.